ANALISIS DAN STUDI KRITIS TERHADAP SYUBHAT NUZUL ISA AL-MASIH DALAM PRESPEKTIF HADIS - Is, Fadhilah (Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACT Prophet Isa alaihissalam is an apostle who was sent by Allah before the Prophet Muhammad sallallaahu 'alaihi wasallam to the Jews by bringing the holy book of the Bible. The people of the Children of Israel wanted to kill and crucify him, but Allah protected him and raised him to the sky. In the Qur'an and Hadith it is stated that among the great signs of the Day of Judgment, namely Allah will send Prophet Isa al Masih back to earth to fight Dajjal with Imam Mahdi. Hadiths that explain the descent of Prophet Isa are numerous, even some scholars classify this hadith as mutawatir, while others consider the hadith ahad as Sahih. However, among contemporary scholars, such as Muhammad Abduh, Hasan Abdullah at-Turabi, Mahmud Shaltut, there are doubts about the quality of the hadith that was revealed by Prophet Isa. Among the arguments they mention, that the quality of this hadith is ahad, mudtharib, the meaning of which is contrary to reason, contradicts the Koran and so on. After analyzing the matan, sanad, opinions of classical and contemporary scholars, the hadith that was revealed by Isa al Masih is an authentic hadith that must be believed by a Muslim.